(untitled) (Journal of the College of Basic Education, 2026)
For a long period, Iran. served as an arena for international. conflict between major powers, most notably between. Great Britain- which controlled the oil-rich regions of southern Iran and the Soviet Union. This rivalry exerted a profound influence on the country’s domestic political landscape. Faced with this reality,. Iranian national forces saw no alternative but to seek the influence of a (Third Force) to counter British and Soviet hegemony. This role was filled by the United States, which presented itself through slogans. championing. independence and the right to self-determination. Consequently, the orientation of Iranian nationalists shifted toward the United States, leading to the formation of political parties and blocs tasked with countering the communist tide and bolstering national independence through the nationalization. of resources, particularly oil. In this context, the Toilers Party of the Iranian Nation was established as an.